Flora in vegetacija makedonske stepe = Flora and Vegetation of the Macedonian Steppe = Flora i vegetacija na makedonskata stepa - Čarni, Andraž (ZRC SAZU, Založba ZRC, 2008)
In the central part of Macedonia, in the triangle between Veles, Štip and Negotino, there is a vast area that is different from the rest of the country. The entire area slightly resembles an undulating sea, as its surface is interrupted by numerous ditches, which makes the region almost impassable.